ANALISIS PENGUKURAN KINERJA BERDASARKAN KEP-100/MBU/2002 PADA PG. DJOMBANG BARU - PRATIWI, GITA (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this research was to analyze the performance of the PG. Djombang Baru period 2008-2011 based on Keputusan Menteri Badan Usaha Milik Negara Nomor: KEP-100/MBU/2002. Object of research conducted at the PG. New Jombang. This type of data is primary data. Data analysis methods used in ratio analysis, operational and administrative measures. Results from this study that the performance levels of PG. New Jombang period 2008-2011 are included in the healthy group, although from 2010 to the year 2011 there are slightly reduced rate.Keywords: Performance Measurement, Financial, Operational Results, Performance Administration